2016
DOI: 10.1039/c6ra10484c
|View full text |Cite
|
Sign up to set email alerts
|

A novel process concept for the three step Boscalid® synthesis

Abstract: Nowadays, the development of chemical processes using environmentally friendly solvents is of high importance. As an alternative to conventional reaction media based on organic solvents, we show a novel aqueous surfactant-based process concept which is used for the three step synthesis of the fungicide Boscalid®. By applying three phase microemulsion systems for the Suzuki coupling reaction, the first step within the Boscalid® synthesis, a simple product and catalyst separation can be achieved, whereby the wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…1 Glasnov et al 5 reported a continuous and efficient method for synthesis of Boscalid, the Suzuki coupling reaction was catalyzed by Pd(PPh 3 ) 4 , the reduction reaction under the catalysis of Pt/C, and condensation reaction under the conditions of microwave heating, the reaction conditions of are harsh. Schwarze et al 15 reported an environmentally friendly solvents for synthesis of Boscalid, the Suzuki reaction was catalyzed by watersoluble homogeneous Pd/SPhos, together with an easily recyclable heterogeneous PtIr@TiO 2 , the condensation reaction under the conditions of triethylamine, the catalysts used are not easily available. Audun Drageset et al 16 reported a three step continuous/semi-flow process for synthesis of Boscalid, the Suzuki coupling reaction was catalyzed by Pd(PPh 3 ) 4 , the reduction reaction was used of NaBH 4 /CoSO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Glasnov et al 5 reported a continuous and efficient method for synthesis of Boscalid, the Suzuki coupling reaction was catalyzed by Pd(PPh 3 ) 4 , the reduction reaction under the catalysis of Pt/C, and condensation reaction under the conditions of microwave heating, the reaction conditions of are harsh. Schwarze et al 15 reported an environmentally friendly solvents for synthesis of Boscalid, the Suzuki reaction was catalyzed by watersoluble homogeneous Pd/SPhos, together with an easily recyclable heterogeneous PtIr@TiO 2 , the condensation reaction under the conditions of triethylamine, the catalysts used are not easily available. Audun Drageset et al 16 reported a three step continuous/semi-flow process for synthesis of Boscalid, the Suzuki coupling reaction was catalyzed by Pd(PPh 3 ) 4 , the reduction reaction was used of NaBH 4 /CoSO 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The catalyst complex stayed in the middle phase. Volovych et al performed Suzuki coupling reactions with Pd/SPhos as the catalyst complex (#13, [57]), and they showed that the reaction performance is stable after ligand addition to each new run to replace the fraction that was extracted. Furthermore, this work shows that the organic excess phase can be used without any pretreatment in subsequent reaction steps.…”
Section: Examples For Catalyst Recyclingmentioning
confidence: 99%
“…The Suzuki coupling reaction was the first step in the synthesis of boscalid. The three-step sequence for the synthesis of boscalid is shown here [57,66]. Furthermore, the synthesis of boscalid was carried out without the isolation of the intermediates resulting in good yield.…”
Section: Examples For Catalyst Recyclingmentioning
confidence: 99%
“…Note that the surfactant film in micellar systems is strongly curved, while its curvature in microemulsions is considerably lower and adjustable suggesting an impact on the orientation of the catalyst complex. Last but not least, the adjustable phase behaviour of both reaction media, but especially of the microemulsions, can be used for product separation and catalyst recycling, as shown for example in the three‐step synthesis of the fungicide boscalid® [16] …”
Section: Introductionmentioning
confidence: 99%